Comparison of educational environments in different sized rural hospitals during a longitudinal integrated clerkship in Thailand - Pairoj Boonluksiri; Tipaporn Thongmak; Boonyarat Warachit (James Cook University, 2021)
Introduction: The longitudinal integrated clerkship (LIC) curriculum model focuses on patient-centered care and continuity of clinical and cultural learning between medical students, patients, clinicians, and a system of care. In rural settings, participating medical students are expected to have an interest in rural medicine and an involvement in the community. Many schools in the USA, Canada, and Australia have implemented LICs in undergraduate programs in different ways. However, a few published reports in Asia are available. This is the first report of a modified rural LIC in Thailand. The objective was to assess the educational environment of a rural LIC using the Dundee Ready Education Environment Measure (DREEM) questionnaire and to compare students' response on the basis of year of study and different sizes of hospitals. Methods: A cross-sectional study was conducted. The study population comprised 75 clinical-year students in 2020. The modified LIC was implemented as part of integrated multidisciplinary rural clerkships for fourth-year students, and for fifth-year students undertaking clinical placements. Clinical clerkships in rural settings took place over 12 weeks for fourth-year students and over 14 weeks for fifth-year students. Practical exposure included the clinical areas of internal medicine, psychiatry, surgery, pediatrics, obstetrics and gynecology, emergency medicine, and family medicine, in outpatient and inpatient settings. The DREEM questionnaire was used to evaluate students' perceptions of learning climate. Data analysis was performed to determine the different size of hospitals and other factors associated with a favorable educational environment. Results: The response rate to the questionnaire was 96%. The overall DREEM score average was 137.7/200. Students' perceptions of learning and of teaching had mean scores of 30.1/48 and 35.7/44, respectively. Students' academic self-perceptions scored 18.7/32. Students' perceptions of atmosphere scored 30.4 of 48, and social self-perceptions scored 18.3/28. The academic subscale had the lowest percentage of scores regarded as confidence in knowledge gain. The factors associated with positive educational environment were staff as principal preceptors and large hospitals. Conclusions: LIC implementation in a community health system is a model for expanding clinical clerkships. Good infrastructure of the host hospital and enthusiastic preceptors are the key success factors. Staff supervision is essential to encourage student learning, especially in academic environments. Large hospitals have better infrastructure to support learning processes than small hospitals.